Menggali Loyalitas Pelanggan: Pengaruh Lifestyle Branding, Persepsi Keadilan Harga, dan Kepuasan Emosional pada Supermarket Pamella Satu - Suhirman, Gatot; Linawati, Linawati (DAS Institute, 2025)
This study uses a qualitative descriptive approach. Its primary objective is to analyze the influence of lifestyle branding, perceptions of price fairness, and emotional satisfaction on customer loyalty at Pamella Satu Supermarket. The subjects of this study are regular customers who shopped more than once during November 2024. Primary data serves as the main source of information for this research. The data was obtained through a questionnaire distributed to Pamella Satu Supermarket customers via Google Forms and shared through the WhatsApp (WA) application. The study's population consists of 100 customers, with a sample size of 80 respondents. The sampling method employed is purposive sampling. The findings from the partial analysis indicate that lifestyle branding does not significantly affect customer loyalty at Pamella Satu Supermarket. However, perceptions of price fairness and emotional satisfaction contribute positively and significantly to customer loyalty. Furthermore, the simultaneous analysis shows that lifestyle branding, perceptions of price fairness, and emotional satisfaction collectively play a positive and significant role in shaping customer loyalty. The Adjusted R Square value of 0.802 indicates that 80.2% of the variation in customer loyalty at Pamella Satu Supermarket is accounted for by lifestyle branding, perceptions of price fairness, and emotional satisfaction. The remaining 19.8% is influenced by other factors not examined in this study.